2008
DOI: 10.1515/cclm.2008.234
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic pattern of plasma in off-pump coronary artery bypass surgery

Abstract: A significant decrease in the expression of three fibrinogen gamma-chain (FGC) isoforms, three vitamin D-binding protein (DBP) isoforms, six haptoglobin (HPT) isoforms, two apolipoprotein (apo)-AI isoforms, one ceruloplasmin (CP) isoform and apoAIV was found after revascularization. Before anastomosis, negative correlations between blood flow and FGC isoforms 2 and 3 and positive correlations between blood flow and apoAI isoform 5 were observed. After anastomosis, we observed positive correlations between hapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A protein array analysis in concert with a gene array analysis confirmed and expanded the knowledge on the proinflammatory mediators released during CPB indicating leukocytes as the promoters of a subsequent inflammatory response . Recently Silva et al using a proteomic approach found that in the blood from coronary sinus the expression of a number of proteins associated with inflammation and vascular protection was modified in the early phases of the off-pump CABG procedure . However, the main actors in this field and, consequently, the ultimate objectives for a targeted drug therapy able to modulate this stress response have not been completely identified yet.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A protein array analysis in concert with a gene array analysis confirmed and expanded the knowledge on the proinflammatory mediators released during CPB indicating leukocytes as the promoters of a subsequent inflammatory response . Recently Silva et al using a proteomic approach found that in the blood from coronary sinus the expression of a number of proteins associated with inflammation and vascular protection was modified in the early phases of the off-pump CABG procedure . However, the main actors in this field and, consequently, the ultimate objectives for a targeted drug therapy able to modulate this stress response have not been completely identified yet.…”
Section: Discussionmentioning
confidence: 97%
“…16 Recently Silva et al using a proteomic approach found that in the blood from coronary sinus the expression of a number of proteins associated with inflammation and vascular protection was modified in the early phases of the offpump CABG procedure. 17 However, the main actors in this field and, consequently, the ultimate objectives for a targeted drug therapy able to modulate this stress response have not been completely identified yet.…”
Section: Discussionmentioning
confidence: 99%
“…The proteomic study was performed by the molecular research team in blinded form. For two-dimensional electrophoresis (2-DE), 500 lg of plasma proteins were used (Mateos-Cáceres et al 2004;López-Farré et al 2007;Silva et al 2008). The plasma samples were loaded on immobilized pH gradient (IPG) strips (18 cm, pH 4-7) and isoelectric focusing was performed using a Protean IEF cell system (Bio-Rad).…”
Section: Two-dimensional Electrophoresis Of Plasma Proteins Image Acmentioning
confidence: 99%